Examining the Proposed Lead and Copper Rule Trigger Level. Issue 11 (3rd November 2020) - Masters, Sheldon V.; Bartrand, Timothy A.; Seidel, Chad J.
Key Takeaways: Draft revisions to the US Environmental Protection Agency's Lead and Copper Rule propose creating a 10 μg/L trigger level of lead concentration in addition to the action level. Although the trigger level might help identify and improve systems operating with marginal corrosion control, it duplicates available regulatory options at the cost of adding a regulatory level. The trigger level could have the unintended consequence of reducing compliance data analysis by systems or regulators that elect to comply with the Lead and Copper Rule when following the minimum regulatory requirements.